Cartilla metodológica para la intervención de inmuebles en el Centro Histórico de Girón: Reflejos del pasado (2023)
The objective of this project is to develop a methodological primer for the architectural intervention of heritage properties in the historic center of the municipality of Girón. To achieve this, a study of the context of the site is carried out based on its heritage declaration, its historical and regulatory context, and includes community participation to establish social design concepts.